(untitled) (Universal xalqaro ilmiy jurnal, 2026)
The aim of this study was to evaluate the changes in cardiac function and hemodynamic parameters in rats during 10-day exposure to Sodium nitrite. The study demonstrated that NaNO₂ exerts a toxicological effect on the organism, induces hypoxic conditions, and, through the production of nitric oxide (NO), causes relaxation of vascular smooth muscle, leading to vasodilation and a decrease in arterial blood pressure. In conclusion, a 10-day NaNO₂ intoxication results in disruption of the cardiovascular system in rats, manifested by a sharp decline in arterial blood pressure and an increase in heart rate. These findings confirm the development of hemodynamic disturbances due to the toxic effect of nitrites.